2017
DOI: 10.1002/cne.24157
|View full text |Cite
|
Sign up to set email alerts
|

Survey of retinal ganglion cell morphology in marmoset

Abstract: In primate retina, the midget, parasol, and small bistratified cell populations form the large majority of ganglion cells. In addition, there is a variety of low-density wide-field ganglion cell types that are less well characterized. Here we studied retinal ganglion cells in the common marmoset, Callithrix jacchus, using particle-mediated gene transfer. Ganglion cells were transfected with an expression plasmid for the postsynaptic density 95-green fluorescent protein. The retinas were processed with establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 96 publications
8
85
0
Order By: Relevance
“…Separate studies on K cells and IPul revealed similar inputs from retinal ganglion cells: Kwan et al (2018) demonstrated that retinal ganglion cells projecting to a sub-division of IPul in the marmoset had widefield morphologies including broad thorny, recursive bistratified, narrow thorny and large bistratified cells. Similar morphologies of retinal ganglion cells have been observed to project exclusively to the K layers of marmoset LGN (Szmajda et al, 2008;Percival et al, 2014;Masri et al, 2017). Two visual pathways from retina to MT via K cells or IPul are alternatives from retino-geniculate-cortical pathway.…”
Section: Discussionsupporting
confidence: 54%
“…Separate studies on K cells and IPul revealed similar inputs from retinal ganglion cells: Kwan et al (2018) demonstrated that retinal ganglion cells projecting to a sub-division of IPul in the marmoset had widefield morphologies including broad thorny, recursive bistratified, narrow thorny and large bistratified cells. Similar morphologies of retinal ganglion cells have been observed to project exclusively to the K layers of marmoset LGN (Szmajda et al, 2008;Percival et al, 2014;Masri et al, 2017). Two visual pathways from retina to MT via K cells or IPul are alternatives from retino-geniculate-cortical pathway.…”
Section: Discussionsupporting
confidence: 54%
“…At least 20 types of RGCs have been classified in marmoset retina (Masri, Percival, Koizumi, Martin, & Grünert, ). As discussed in that study, the different types can be distinguished based on their dendritic field size, morphology, and stratification in the inner plexiform layer.…”
Section: Resultsmentioning
confidence: 99%
“…So far, no physiological recordings of direction-selective cells have been published (but see [50]) and we could not detect such direction-selective behavior in our data set either (data not shown). Morphological studies identified potential candidates for primate direction-selective neurons [23,51,52]. These cells have a large dendritic field and hence they are much fewer in number than the smaller midget or parasol cells.…”
Section: Absence Of Direction-selective Cellsmentioning
confidence: 99%